Development of a Fundamental Movement Skill Program based on Augmented Reality Technology for Elementary School Students - Sugita Krisdian; Febi Kurniawan; Resty Gustiawati (UNIB Press, 2024)
Basic movement is very influential for children's survival because when children have good basic movement skills it will encourage their consistent patterns in carrying out physical activities. After that, physical activity carried out regularly is what will encourage a healthy quality of life and will ultimately help them in their daily movement tasks. The aim of this research is to develop a Fundamental Movement Skill Learning Program Based on Augmented Reality Technology for Elementary School Students which is based on the National Sports Grand Design Master Plan (DBON) Program which has a similar mission, namely the realization of active student participation in sports to achieve the physical fitness level of Indonesian students. The research method used in this research was the ADDIE Development model and the product was validated by three Validators, namely teachers and two expert lecturers in Physical Education and implemented at SDN Margakaya I with expert assessment results having an average of 87.3%, and the results of program implementation in the field. In general, this program is considered feasible.